Neorealism and neoliberalism the contemporary debate - Baldwin, David A. (New directions in world politics, 1993)
This study constructs various theories of post-Cold War world politics. It presents the Realist position, which asks whether the end of the Cold War brings a higher risk of military conflict, as well as the Institutional view, which argues that international co-operation is now possible.